A demonstration of the FN packet marking probability - M. Kadhum, Mohammed; Hassan, Suhaidi (2009)
The effectiveness of queue management mechanisms relies on how good their control decisions will help in satisfying their goals regarding congestion avoidance and control.These decisions are implemented and compelled during the design of the packet mark probability and the mark activation functions. The design of Fast Congestion Notification (FN) drop/mark probability function enables the two control decisions, packet admissions and congestion control directing, to be made along with each other. This permits sending congestion avoidance notification as early as required even if the queue is almost empty, and preventing congestion notification even if the queue is almost full but the arrival rate is controllable. This leads to good buffer utilization and proper congestion detection. This paper demonstrates the drop/mark probability functions that the fast FN policy would exercise for different values of optimal queue size, and also for a specific optimal queue size value.